印尼本土华文教材《梅花》中华文化与印尼文化内容分析ANALYSIS ON CHINESE ANDINDONESIANCULTURE CONTENT OF INDONESIANLOCALCHINESE LANGUAGE STUDY MATERIALSMEIHUA - Wibowo, Gunawan (Asosiasi Program Studi Mandarin Indonesia, 2025)
摘要：语言是人类交际的工具，同时也是文化的载体。因此，学习某种外语时，不能不学习目的语国家的文化。而教材是华文教学中三教要素（即教师、教材、教法）之一，华教中这三者都不能缺少。由此可见，华文教材在一定的程度上有必要介绍中华文化。通过文献调查，笔者将从文化方面的十几个部分分析印尼本土小学华文教材《梅花》，找出它的文化内容大纲，并解析其编写是否符合华文教材编写原则的要求。此使该教材的文化内容更加完善，也有助于有意编写本土华文教材者提供参考依据。关键词：印尼本土华文教材，《梅花》，文化内容，分析Abstract: Language is s human’s communication tool. At the same time, it is alsothereflection of the culture. As a result, when learning a foreign language, we must also learntheculture of that foreign country. One of the main three key elements (those are the teacher, thestudy material and the teaching method) in teaching Chinese as a foreign language is thestudymaterials. In teaching Chinese as a foreign languge, these three key elements are indispensible. The study materials of teaching Chinese as a foreign language should reflect the Chineseculture. Through literature investigation, the writer analyzes some cultural aspects of local Chinese language study material, all of which compiled in a book series entitled “Meihua”, finds out the culture content’s outline of these study materials and analyze whether itscompiling is fulfill the requirements of Chinese language study materials compiling principles, so that the culture content of these study materials can be more perfect, and it canalsopeovide some basic references to those who are willing to compile a set of local Chineselanguage study materials. Keywords: Indonesian local Chinese language study materials；Meihua；culture content；analysis